Surviving the Gang Bang theory of nature: The environment movement during the Howard years - Doyle, Timothy (Routledge, 2010)
This article investigates the Australian environment movement during the Howard years, 1996–2007. First, the author maps out key issues which emerged during this period of governance, and then focuses on outlining the strategic and tactical repertoire of the movement at this time. The author argues the case that the movement embraced a neoliberal ideology often expressed within the dominant discourses shared by the state and big business, as the movement sought to operate more and more on business principles. In addition, environmentalists pursued a neoconservative moral agenda, so typical of the Howard years, right across the policy-making realm. Finally, the article concludes with the argument that the Australian green movement, mistaking a neoliberal geo-economic agenda as postmodernity, reorganized itself in such a way as to deliver political wins to its traditional adversaries, fundamentally weakening its position within Australian society as an advocate of radical social change.